Green and scalable synthesis of nanocrystalline kuramite - Giaccherini, Andrea; Cucinotta, Giuseppe; Martinuzzi, Stefano; Berretti, Enrico; Oberhauser, Werner; Lavacchi, Alessandro; Lepore, Giovanni Orazio; Montegrossi, Giordano; Romanelli, Maurizio; De Luca, Antonio; Innocenti, Massimo; Moggi Cecchi, Vanni; et al. (Beilstein Journal of Nanotechnology, 2019)
The new generation of solar cells aims to overcome many of the issues created by silicon-based devices (e.g., decommissioning, flexibility and high-energy production costs). Due to the scarcity of the resources involved in the process and the need for the reduction of potential pollution, a greener approach to solar cell material production is required. Among others, the solvothermal approach for the synthesis of nanocrystalline Cu–Sn–S (CTS) materials fulfils all of these requirements. The material constraints must be considered, not only for the final product, but for the whole production process. Most works reporting the successful synthesis of CTS have employed surfactants, high pressure or noxious solvents. In this paper, we demonstrate the synthesis of nanocrystalline kuramite by means of a simpler, greener and scalable solvothermal synthesis. We exploited a multianalytical characterization approach (X-ray diffraction, extended X-ray absorption fine structure, field emission scanning electron microscopy, Raman spectroscopy and electronic microprobe analysis (EMPA)) to discriminate kuramite from other closely related polymorphs. Moreover, we confirmed the presence of structural defects due to a relevant antisite population.
Keywords: Cu2ZnSnS4 (CZTS); Cu3SnS4 (CTS); green chemistry; kuramite; photovoltaic materials; solvothermal synthesis